EFEKTIVITAS PENERAPAN METODE DEMONSTRASI TERHADAP PERMAINAN MUSIK ANSAMBEL PADA SISWA KELAS VII - Arry, Cornelius; Fretisari, Imma; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research aims to determine the effectiveness of implementing the demonstration method towards the ensemble music games for seventh grade students at SMPN 2 Bengkayang. This study uses a quantitative approach and the method is a true experimental and the design is the pretest-posttest control group design. The sample were students of VII A (experimental class) as many as 41 pupils, of VII B (control class) as many as 41 pupils. Data collection techniques that used are observation techniques and measurement techniques. Meanwhile, the technique used to analyze the data is descriptive and statistical analysis by looking at averages and   t?test. Based on the results of data analysis on the effectiveness of the implementing the demonstration methods towards ensemble music games on seventh grade students obtained t_(count 3) of 13.48. As for the value of table with a significance level of 5% for two sides with db = 80, then obtained at 1.99. Since the value of t_(count 3) ? t_tabel, then the null hypothesis is denied. It means that there is a significant difference and the effectiveness of implementing the demonstration method towards the activeness of  ensemble music playing on seventh grade students of SMPN 2 Bengkayang.  Keywords: Demonstration Method, Ensemble Music Games